Atresia Ani Associated with Rectovaginal Fistula in a Crioulo Filly - Dors Almeida, Henrique; Faé, Alice; Pioner de Jesus, Bruna; Alberto Machado, Guilherme; Parizotti, Renan Felipe; Gerardi Bernardo, Paula; Rechembak Marchese, Paola; Barreto Coelho, Ana Carolina (Acta Scientiae Veterinariae, 2025)
Background: Atresia ani is a congenital malformation of the gastrointestinal tract caused by incomplete embryonic development. It can result from congenital anomalies or environmental factors. The gastrointestinal, urinary, and reproductive tracts share an embryonic origin, and their development involves the separation of these systems and subsequent rupture of the anal membrane to form the anus. Atresia ani occurs when this membrane fails to perforate. In some instances, it is accompanied by other anomalies, such as rectovaginal fistulas. Reports of atresia ani with rectovaginal fistula in horses are rare, and no cases have been documented in Crioulo mares. Case: A Crioulo filly presented with a history of defecation through the vulva. Clinical examination revealed the absence of an anal opening and the presence of a rectovaginal fistula. Surgical intervention was recommended and performed in two stages: closure of the rectovaginal fistula and creation of an anal orifice. Preoperative preparation included the administration of mineral oil, laxatives, and enemas to facilitate fecal transit. During the surgery, an enema with warm water was administered to remove fecal matter, followed by antisepsis. The procedure was performed in two stages: (1) closure of the rectovaginal fistula and (2) creation of an anal orifice. To repair the fistula, an incision was performed in the perineal region, and the tissues were dissection to expose the fistula. Two layers of sutures were applied—one along the rectal floor and the other along the vaginal roof—to isolate the structures. The communication between the rectum and vagina was severed by making an incision between the suture layers. Subsequently, a skin incision was made to access the rectal wall. The rectum was reconstituted, and the intestinal wall was anchored to the anal mucosa to restore the physiological pathway for fecal passage. Postoperative management included the use of a probe to administer mineral oil and regular enemas to facilitate defecation and minimize pressure on the suture sites. Two days after the surgery, the patient exhibited difficulty defecating and developed perineal prolapse due to the strain exerted by the fecal content at the fistula site; this led to suture dehiscence and the reopening of the rectovaginal canal, necessitating a second surgical intervention. All preoperative procedures from the initial intervention were repeated. However, 1 day before the second surgery, the patient showed signs of colic. Exploratory laparotomy revealed small colon impaction. The patient's condition deteriorated significantly during postoperative recovery, resulting in death 3 days after surgery. Discussion: This case describes a Crioulo filly diagnosed with type II atresia ani and a rectovaginal fistula. The diagnosis was based on clinical signs and anatomical abnormalities identified during physical examination. This rare condition in horses is more commonly observed in calves and piglets. Rectovaginal communication allowed the filly to defecate through the vulva despite the absence of an anal orifice, which was the only clinical sign. Surgical correction involved fistula repair and anal membrane perforation to separate the systems. However, postoperative complications, including suture dehiscence, led to poor outcomes. The prognosis for atresia ani remains guarded due to the high risk of postoperative complications. Keywords: congenital, equine, malformation, pathology. Título: Atresia ani associada à fístula retovaginal em uma potra da raça Crioula Descritores: congênito, equino, má formação, patologia.